2007
DOI: 10.1210/en.2006-0835
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor-I Is an Important Antiapoptotic Factor for Rat Leydig Cells during Postnatal Development

Abstract: The present investigation examines the influence of IGF-I and the role of IGF-I receptor (IGF-IR) in the apoptosis/survival of Leydig cells. Immunohistochemical analysis of the rat testis at different ages revealed that the level of the phosphorylated IGF-IR increases from birth to d 20 of postnatal life, remaining high in the adult testis. Western blotting revealed that this level is higher in Leydig cells isolated from 40-d-old than from 10- or 60-d-old rats. Application of the terminal deoxyribonucleotidyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
48
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 43 publications
5
48
1
Order By: Relevance
“…Although PPP inhibits IGF-1-induced IGF-1R phosphorylation Vasilcanu et al, 2004;Colón et al, 2007;Conti et al, 2007), the present results suggest that PPP induces IGF-1R ubiquitination without receptor phosphorylation. Because IGF-1R phosphorylation is required for its ubiquitination , the existence of a causal relationship between the two actions of PPP on IGF-1R seems to be uncertain.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…Although PPP inhibits IGF-1-induced IGF-1R phosphorylation Vasilcanu et al, 2004;Colón et al, 2007;Conti et al, 2007), the present results suggest that PPP induces IGF-1R ubiquitination without receptor phosphorylation. Because IGF-1R phosphorylation is required for its ubiquitination , the existence of a causal relationship between the two actions of PPP on IGF-1R seems to be uncertain.…”
Section: Discussioncontrasting
confidence: 60%
“…PPP inhibits activity of IGF-1R Vasilcanu et al, 2004Vasilcanu et al, , 2006Ulfarsson et al, 2005;Strömberg et al, 2006;Colón et al, 2007;Conti et al, 2007;Guha et al, 2007;Razuvaev et al, 2007;Shields et al, 2007) but also down-regulates the receptor (Vasilcanu et al, 2008). Even though PPP may have other effects, we conclude that it does not cross-target the highly homologous insulin receptor .…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Moreover, PPP reduced phosphorylation of Akt, induced caspase 3 activation and apoptosis and caused tumor regression in grafted mice Vasilcanu et al, 2004;Catrina et al, 2005;Ulfarsson et al, 2005;Conti et al, 2007;Menu et al, 2006;Stromberg et al, 2006;Tomizawa and Saisho, 2006;Vasilcanu et al, 2006;Colon et al, 2007;Razuvaev et al, 2007). PPP did, however, not affect growth of established R-vsrc (IGF-1RÀ/À) tumor grafts , suggesting selectivity for IGF-1R regarding tumor growth.…”
Section: Introductionmentioning
confidence: 95%
“…It has been suggested that IGF-I can influence Leydig cell survival and proliferation (40,41). Moreover, it has been shown that IGF-I up-regulates aromatase expression in primary cultures of rat Leydig cells through a cAMP-independent mechanism (42).…”
Section: Discussionmentioning
confidence: 99%